2017
DOI: 10.1021/acs.energyfuels.7b03167
|View full text |Cite
|
Sign up to set email alerts
|

Self-Heating of Agricultural Residues During Storage and Its Impact on Fuel Properties

Abstract: The present work aimed to investigate the self-heating process of agricultural residues during storage and to evaluate its impact on the properties of the stored fuels. Two types of biomass, rice straw and husk, were used as raw materials. Their self-heating processes and characteristics were investigated by storing the materials with different moisture contents and particle sizes in a bench-scale reactor and monitoring the evolution of inside temperatures. The resulting materials were systematically character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Ying et al [ 136 ] also studied the preparation of straw magnesium cement (SMC) from rice straw, another bio-based isolation material. In addition, studies have proven that rice straw is easier to self-heat than rice husk, which triggers the occurrence of spontaneous combustion in biofuels [ 137 ]. This difference is caused by chemical composition, physical properties, bulk density and surrounding environment.…”
Section: Polymer-based Flame-retardant Composites and Application In Construction Engineeringmentioning
confidence: 99%
“…Ying et al [ 136 ] also studied the preparation of straw magnesium cement (SMC) from rice straw, another bio-based isolation material. In addition, studies have proven that rice straw is easier to self-heat than rice husk, which triggers the occurrence of spontaneous combustion in biofuels [ 137 ]. This difference is caused by chemical composition, physical properties, bulk density and surrounding environment.…”
Section: Polymer-based Flame-retardant Composites and Application In Construction Engineeringmentioning
confidence: 99%
“…For example, oxidation and microbial degradation during storage can produce more C−O groups on carbohydrate surfaces. 210 (2) At the macromolecule level, the bond formation and cleavage taking place during storage, and preprocessing can cause condensation of the macromolecules. For example, lignin tends to migrate and condense when the attached hemicellulose is removed by dilute acid pretreatment.…”
Section: Hammer Millmentioning
confidence: 99%
“…The physical properties of biomass feedstocks emerge from their underlying macromolecular interactions, which can undergo substantial changes across multiple length scales during the harvest, storage, and preprocessing and conversion processes: (1) At the subnanometer level, the functional groups on carbohydrates and lignin can be significantly modified during storage and pretreatment. For example, oxidation and microbial degradation during storage can produce more C–O groups on carbohydrate surfaces . (2) At the macromolecule level, the bond formation and cleavage taking place during storage, and preprocessing can cause condensation of the macromolecules.…”
Section: Other Featured Analytical Techniquesmentioning
confidence: 99%
“…The seasonal biomass supply requires a storage process to ensure the year-round availability. However, depending on moisture content, bale storage could present favorable conditions for microbial growth, biological heating, and biomass degradation, which results in feedstock loss, quality changes, and risks to downstream conversion processes and worker health and safety. Field studies have observed that the aged biomass generated by storage can reduce bale integrity. , Biological heating can alter composition and cell wall structures that are manifest in macro-scale mechanical properties.…”
Section: Introductionmentioning
confidence: 99%